How modality specific is processing of auditory and visual rhythms?. (13th October 2015) - Pasinski, Amanda C.; McAuley, J. Devin; Snyder, Joel S.
Abstract: The present study used ERPs to test the extent to which temporal processing is modality specific or modality general. Participants were presented with auditory and visual temporal patterns that consisted of initial two‐ or three‐event beginning patterns. This delineated a constant standard time interval, followed by a two‐event ending pattern delineating a variable test interval. Participants judged whether they perceived the pattern as a whole to be speeding up or slowing down. The contingent negative variation (CNV), a negative potential reflecting temporal expectancy, showed a larger amplitude for the auditory modality compared to the visual modality but a high degree of similarity in scalp voltage patterns across modalities, suggesting that the CNV arises from modality‐general processes. A late, memory‐dependent positive component (P3) also showed similar patterns across modalities.